High school students' attitudes towards geography: An indicator of the need for innovative approaches in geography teaching - Vuletić Jovana; Miletić Milan (Zbornik Radova: Geografski Fakultet Univerziteta u Beogradu)
The importance of geography lessons lies in the fact that we learn something about the space in which we live, which is important for all people regardless of their interests. A student's interest in a subject and thus the acquisition of its content depends on the student's attitude towards the subject. For this reason, this study examines the attitudes of secondary school students towards the subject of geography, which differ in terms of their subject of study, their favourite subject and the faculty in which they would like to enrol. The data collected with the questionnaire was processed with the statistical software SPSS 26.0. The neutral attitude of the students towards geography as a subject indicates that geography teaching needs to be modernised and carried out using modern teaching methods. The application of teaching innovations in geography lessons would contribute to greater student interest in geographical content and thus to better student performance in this subject.